Molecular cluster magnets - Winpenny, Richard (World Scientific series in nanoscience and nanotechnology, 2012)
This work covers new developments in the field of molecular nanomagnetism, complementing previous books in this area (for example the volume by Gatteschi, Sessoli and Villain on Single Molecule Magnets). The book is written by experts in the field and is intended as a compilation of critical reviews of new areas rather than a comprehensive text.